Spy Hunt (Scooby-Doo! Picture Clue Book) - Barbo; Maria S. (New York Scholastic, 2004)
Scooby and Shaggy are playing spies. But now there is a real mystery. Where is Daphne? Can they solve this case? And will someone give them Scooby Snacks?